ASPEK-ASPEK POLITIK, EKONOMI, SOSIAL DAN BUDAYA DALAM PENDIDIKAN: PENDIDIKAN DALAM PERSPEKTIF POLITIK DI INDONESIA - Dikson Silitonga (ESENSI: Jurnal Manajemen Bisnis, 2010)
The advance of education in a country is determined by many factors, such as ; politic, economy, culture and society of that nation. Education and politic are two essential elements for political society in every nations. A nation of which the educational politic is bad, it will perform a bad educational quality, too. On the other hand, a nation that has good educational politic, the performance will be good. Both of them have a role to form the social character in a nation. Meanwhile, in democracy and decentralization in Indonesia, the politic (executive and legislative ) has a great influence. Therefore, politic and authority (power) can be a media for public expectation for good educational system. Hence, we need serious action to create educational politic situation which is good and solid by the executive and legislative to achieve the education which has good quality and spreads in districts in Indonesia.Key words : Education, Politic, Authority, Key of Success, Democratization, Decentralization, Educational Politic Condition.